2021
DOI: 10.3390/molecules26185566
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Tests for a Rapid Evaluation of Antidiabetic Potential of Plant Species Containing Caffeic Acid Derivatives: A Validation by Two Well-Known Antidiabetic Plants, Ocimum gratissimum L. Leaf and Musanga cecropioides R. Br. ex Tedlie (Mu) Stem Bark

Abstract: Plant bioactive extracts represent a major resource for identifying drugs and adjuvant therapy for type 2 diabetes. To promote early screening of plants’ antidiabetic potential, we designed a four in vitro tests strategy to anticipate in vivo bioactivity. Two antidiabetic plants were studied: Ocimum gratissimum L. (Oc) leaf extract and Musanga cecropoides R. Br. ex Tedlie (Mu) stem bark extract. Chemical compositions were analyzed by LCMS and HPLC. Antidiabetic properties were measured based on (1) INS-1 cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Thus if the major finding of this research is translatable to human, extract of Ocimum gratissimum may be beneficial as a nutritional supplement in the prevention of aspartame induced renal insufficiency. Although the beneficial effects of Ocimum gratissimum extract in some human ailments using animal models have been documented in chemical liver injury [25], diabetes mellitus [26], bacterial infections [27] and human cancer cell lines [28][29][30] but not in relation to aspartame and chronic kidney disease. The outcome of this study is the first documented evidence of the beneficent of O. gratissimum in aspartame induced kidney insufficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Thus if the major finding of this research is translatable to human, extract of Ocimum gratissimum may be beneficial as a nutritional supplement in the prevention of aspartame induced renal insufficiency. Although the beneficial effects of Ocimum gratissimum extract in some human ailments using animal models have been documented in chemical liver injury [25], diabetes mellitus [26], bacterial infections [27] and human cancer cell lines [28][29][30] but not in relation to aspartame and chronic kidney disease. The outcome of this study is the first documented evidence of the beneficent of O. gratissimum in aspartame induced kidney insufficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, both extracts and the EO were sources of polyphenols. For example, the measured total phenolic content in Z. tenuior was equal to 49.0 ± 1.4 mg mg gallic acid/100 g of EO [15].…”
Section: Chemical Composition Of Extracts By Hplc-esi-qtof-ms/msmentioning
confidence: 97%
“…Both Ziziphora species were also rich in phenolic compounds. These authors investigated the antibacterial activity of EOs against important foodborne pathogenic bacteria and showed that they could be considered as good sources of natural antibacterial material as well as food preservative [2,15].…”
Section: Candida Glabratamentioning
confidence: 99%
“…"A recent study revealed the ethanolic leaf extract of M. cecropioides to possess both anti-inflammatory and anti-nociceptive effect. In vitro and in vivo hypoglycemic properties of the leaf and stem bark have also been reported" [16]. Since imbalance in oxidative stress has been implicated in the complications of diabetes and multiple organ failure from chemical/xenobiotics toxicities, this study investigated the effect of the leaf extract and fractions of M. cecropioides on both chemical and diabetes induced oxidative stress.…”
Section: Musanga Cecropioidesmentioning
confidence: 99%